2017 Handbook of IMF Facilities for Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
This Handbook provides guidance to staff on the financial facilities and non-financial instruments for low-income countries (LICs), defined here as all countries eligible to obtain concessional financing from the Fund. It updates the previous version of the Handbook that was published in February 2016 (IMF, 2016d) by incorporating modifications resulting from Board papers and related decisions since that time, including Financing for Development-Enhancing the Financial Safety Net for Developing Countries-Further Considerations (IMF, 2016c), Review of Poverty Reduction and Growth Trust - Review of Interest Rate Structure (IMF, 2016b), Eligibility to Use the Fund's Facilities for Concessional Financing (IMF, 2017a), Large Natural Disasters-Enhancing the Financial Safety Net for Developing Countries (IMF, 2017b) and Adequacy of the Global Financial Safety Net - Proposal for a New Policy Coordination Instrument (IMF, 2017c). Designed as a comprehensive reference tool for program work on LICs, the Handbook also refers, in summary form, to a range of relevant policies that apply more generally to IMF members. As with all guidance notes, the relevant IMF Executive Board decisions, including the terms of the various LIC Trust Instruments that have been adopted by the Board, remain the sole legal authority on the matters covered in the Handbook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet